Konsep dan Implementasi Kurikulum MBKM (Merdeka Belajar Kampus Merdeka) - Deni Sopiansyah; Siti Masruroh; Qiqi Yuliati Zaqiah; Mohamad Erihadiana (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The objective of the Independent Learning Campus policy is to encourage students to master various fields of science with their fields of expertise, so that they are ready to compete in the global world. This policy provides an opportunity for students to choose the courses they will take based on their own wishes. The implementation of the Independent Learning Policy on the Independent Campus encourages the learning process in higher education to be more autonomous and flexible. Education always strives for the creation of students who always make updates for the sake of renewal at all times. Not only able to be highly educated but able to become agents of change in small and large scope. From the changes and innovations produced, they are able to provide maximum contribution to the progress of a nation that has quality human resources. In writing this paper, the author uses a qualitative research method using a library approach. According to Kirk and Miller.